Análise do processo dos pedidos de recurso dos estudantes de graduação da UFSCar - Durães, Rubens Roberto da Palma (Universidade Federal de São Carlos, 2020)
The General Regiment of Undergraduate Courses at the Federal University of São Carlos - UFSCar reserves the right to ask the Undergraduate Dean regularly to analyze and reconsider, through appeal, situations such as loss of vacancy, problems with enrollment in curricular activities, locking the course out of time and other demands. This right is also guaranteed to those who have lost their connection with the university within a period of up to one year. This research was dedicated to studying the process of analysis of the appeal requests presented by the students, both in the way it is carried out, and in the data that can be extracted from the forms presented by the applicants. The processes used in the second semester of 2018 and in the first and second semesters of 2019 were mapped and analyzed, which allowed a comparison based on the changes that occurred in its stages and tasks and the indication of advantages and disadvantages in these models. Data were also collected through documentary analysis of the resources, attachments and orders presented in the second semester of 2018 and the first semester of 2019, which allowed to outline the profile of the requesting students, list their demands and quantify the responses to their requests, in addition to identify the incidence of these occurrences by Academic Units. After mapping the processes and studying a theoretical framework on Management by Processes, a new format was indicated, with the inclusion of thirteen proposals for improvement in terms of execution, control and improvement. The study also allowed a reflection on public management in higher education and the current management model at UFSCar.
Analysis of the process of appeal requests of undergraduated students at UFSCar
Keywords: Análise de recursos de estudantes; Gestão acadêmica no ensino superior; Gestão por processo; Reintegração de vaga na Graduação; Student appeal analysis; Academic management in higher education; Process management; Reintegration of vacancy in Undergraduate; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS